Unlocking Firm Value Indonesia's Intellectual Capital Triumphs, Risk Management Falters: Membuka Nilai Perusahaan Modal Intelektual Indonesia Berjaya, Manajemen Risiko Terganjal - Sigit Hermawan; Masruroh, Dewi (Indonesian Journal of Law and Economics Review, 2024)
This study examines the impact of Intellectual Capital Disclosure (ICD) and Enterprise Risk Management Disclosure (ERMD) on the value of mining companies listed on the Indonesia Stock Exchange (IDX) from 2017 to 2021, with financial performance as an intervening variable. Using purposive sampling, data from 12 companies were analyzed with SPSS 26. The results show that ICD positively affects both firm value and financial performance, while ERMD negatively impacts both. Financial performance enhances firm value but does not mediate the ICD-firm value relationship; it does mediate the ERMD-firm value relationship. These findings highlight the importance of ICD for improving firm performance and value, suggesting areas for future research to extend the study period and include more variables. Highlight: ICD Impact: ICD significantly boosts firm value and financial performance. ERMD Effect: ERMD negatively influences firm value and financial performance. Financial Mediation: Financial performance mediates ERMD-firm value but not ICD-firm value. Keywoard: Intellectual Capital Disclosure, Enterprise Risk Management, Financial Performance, Firm Value, Mining Companies